2023
DOI: 10.1111/nph.19097
|View full text |Cite
|
Sign up to set email alerts
|

The Medicago truncatula nodule‐specific cysteine‐rich peptides, NCR343 and NCR‐new35 are required for the maintenance of rhizobia in nitrogen‐fixing nodules

Abstract: Summary In the nodules of IRLC legumes, including Medicago truncatula, nitrogen‐fixing rhizobia undergo terminal differentiation resulting in elongated and endoreduplicated bacteroids specialized for nitrogen fixation. This irreversible transition of rhizobia is mediated by host produced nodule‐specific cysteine‐rich (NCR) peptides, of which c. 700 are encoded in the M. truncatula genome but only few of them have been proved to be essential for nitrogen fixation. We carried out the characterization of the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 52 publications
(133 reference statements)
2
12
0
Order By: Relevance
“…The morphology and bacterial occupancy of genome edited nodules were in agreement with the nodulation phenotype of Mtsym19 and Mtsym20 nodules defective in NCR-new35 13 . These results also revealed that NCR-new35 is crucial for the symbiotic interactions not only between M. truncatula 2HA and S. medicae WSM419 but between M. truncatula R108 and S. meliloti FSM-MA as well.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…The morphology and bacterial occupancy of genome edited nodules were in agreement with the nodulation phenotype of Mtsym19 and Mtsym20 nodules defective in NCR-new35 13 . These results also revealed that NCR-new35 is crucial for the symbiotic interactions not only between M. truncatula 2HA and S. medicae WSM419 but between M. truncatula R108 and S. meliloti FSM-MA as well.…”
Section: Resultssupporting
confidence: 70%
“…To increase the e cacy of targeted mutagenesis by CRISPR/Cas9, the Arabidopsis U6-26 promoter was replaced with MtU6.6 in the pKSE401-RR resulting in the vector pKSE466-RR. We inserted the sgRNAs NCR169a and another one, targeting the NCR-new35, of which requirement for effective symbiosis has been recently demonstrated 13 , into pKSE466-RR, respectively. To validate the e ciency of the pKSE466-RR vector construct, the empty vector and pKSE466-RR-NCR169a were introduced into wild-type M. truncatula 2HA plants using A. rhizogenes-mediated hairy root transformation and plants were inoculated with S. medicae WSM419.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations